A case of tracheal foreign body encountered in a Kangal dog: clinical, radiological, endoscopic findings and treatment (FAVE Sección Ciencias Veterinarias, 2021)
The subject of this study was a dog brought to our clinic with complaints of severe cough, dyspnea and anorexia. During the clinical examination, a hard mass was detected by palpation of the neck area. Vomiting reflex was observed. As a result of radiographic and endoscopic examination, a foreign body was found in the caudal part of the larynx. After the diagnosis was made, the patient was anesthetized and the foreign body was removed with forceps from the oral cavity. During the postoperative period, the patient was administered parenteral antibiotics and intraoral antiseptic for a week. The approach to foreign body cases in the respiratory tract of dogs is discussed.
Keywords: foreign body; endoscopy; dog; trachea